PANDANGAN NORMATIF TERHADAP FATWA MUI TENTANG PELARANGAN SHOLAT JUMAT DI MASA PANDEMI COVID-19 (IBTIKAR: Jurnal Studi Islam dan Sosial, 2025)
This study aims to analyze and describe the normative perspective on the fatwa of the Indonesian Ulema Council (Majelis Ulama Indonesia/MUI) regarding the prohibition of Friday prayers during the COVID-19 pandemic. This issue has become a significant concern, considering that Friday prayer is a religious obligation (wajib) for every adult male Muslim who meets the prescribed conditions. However, the global health emergency requires adjustments in the performance of religious practices to safeguard the lives of the Muslim community. The primary data in this research is the MUI Fatwa Number 14 of 2020 concerning the Organization of Worship in Situations of the COVID-19 Outbreak, which serves as the main reference for the discussion. This study employs a qualitative method with a normative approach, which involves an in-depth examination of Islamic legal sources (dalil syar’i) that form the basis of the fatwa. Data collection techniques include document study using observation and note-taking methods on fatwa texts, Islamic legal literature, and other relevant references. The collected data were analyzed using content analysis to explore the normative arguments utilized by MUI in formulating the fatwa. The findings reveal that, normatively, the obligation of Friday prayer is definitive (qat’iy) as stated in the Qur'an and the Hadith of Prophet Muhammad (peace be upon him). Neglecting Friday prayers three consecutive times without a valid excuse is considered a major sin that approaches disbelief (kufr). However, in emergency situations such as a pandemic, Islamic law provides legal concessions (rukhsah) based on the principles of maqashid al-shari’ah, particularly in safeguarding human life (hifz al-nafs). In its fatwa, MUI based its decision on fiqh principles such as al-dharurat tubih al-mahdhurat (necessity permits the prohibited) and la dharara wa la dhirar (no harm should be inflicted or reciprocated). Therefore, the temporary prohibition of Friday prayers in areas categorized as high-risk COVID-19 zones is legally justified as a form of ijtihad (legal reasoning) by scholars aimed at preserving public welfare (maslahah). This research asserts that the MUI fatwa on the prohibition of Friday prayers during the COVID-19 pandemic reflects the flexibility of Islamic law in responding to emergency situations, without neglecting its normative legal principles. Consequently, a comprehensive understanding of normative sources and social contexts is essential to prevent the community from falling into a narrow dichotomy between textualism and contextual realities.